2018
DOI: 10.1145/3231937
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Adaptively Rank Document Retrieval System Configurations

Abstract: Modern Information Retrieval (IR) systems have become more and more complex, involving a large number of parameters. For example, a system may choose from a set of possible retrieval models (BM25, language model, etc.), or various query expansion parameters, whose values greatly in uence the overall retrieval effectiveness. Traditionally, these parameters are set at a system level based on training queries, and the same parameters are then used for di erent queries. We observe that it may not be easy to set al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 69 publications
1
25
0
Order By: Relevance
“…The former is a well-known pairwise LTR algorithm that optimizes the pairwise-loss over the training instances. We choose the second algorithm, RF, as a representative for the RankLib software package 7 , as it has been shown to be the best LTR method among various competitors in a recent study (Deveaud et al, 2019). Our preliminary experiments also revealed that it is the best performing RankLib method in our setting.…”
Section: Methodsmentioning
confidence: 97%
“…The former is a well-known pairwise LTR algorithm that optimizes the pairwise-loss over the training instances. We choose the second algorithm, RF, as a representative for the RankLib software package 7 , as it has been shown to be the best LTR method among various competitors in a recent study (Deveaud et al, 2019). Our preliminary experiments also revealed that it is the best performing RankLib method in our setting.…”
Section: Methodsmentioning
confidence: 97%
“…Indeed, if the difficulty of a query could be predicted, this knowledge could be used to enhance the system querydocument matching one those only queries, by adding some processes such as query disambiguation [4], [6], [17], selective query expansion [8], [20], or matching parameter selection [7].…”
Section: Related Workmentioning
confidence: 99%
“…It is evident that even the state-of-the-art OCR method [6] fails to extract precise information from figures, tables, and formulas. Another application of such page object detection methods is document retrieval systems [7,8], where a document image having a specific type of page object is required. Therefore, it is essential to develop approaches that can parse the information from these page objects.…”
Section: Introductionmentioning
confidence: 99%